2019
DOI: 10.3389/fpsyg.2019.00407
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Online Flow Across Cultures: A Two-Fold Measurement Invariance Study

Abstract: The association between online Flow and Internet Gaming Disorder (IGD) has attracted significant attention. Despite the consensus that online Flow plays a pivotal role in the development of IGD and other Internet addictive behaviors, there has been a lack of consistency in measurement scales used to assess online Flow. Even widely used measures of online Flow have not been psychometrically assessed across culturally diverse populations of gamers. Such an assessment would enhance the accuracy of cross-cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 114 publications
(227 reference statements)
1
8
0
Order By: Relevance
“…This is inseparable from the lack of control that teachers can give to individuals when learning takes place. If individuals can regulate themselves well, individuals will avoid internet abuse and show good selfefficacy (Hu et al, 2019;Lee, Watson), & Watson, 2020;Odaci, 2011). The higher the academic self-efficacy in the individual, the higher the academic flow in online learning experienced by the individual (Diola & Mudjiran, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is inseparable from the lack of control that teachers can give to individuals when learning takes place. If individuals can regulate themselves well, individuals will avoid internet abuse and show good selfefficacy (Hu et al, 2019;Lee, Watson), & Watson, 2020;Odaci, 2011). The higher the academic self-efficacy in the individual, the higher the academic flow in online learning experienced by the individual (Diola & Mudjiran, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that there is a connection between traits of loyalty, selfesteem [15,16], self-construal [12] neuroticism [17] coping style [18] agreeableness, emotional stability, personality, specifically conscientiousness [19,20] and problematic Internet use. However, one of the factors that play an important role in the development of problematic Internet use in individuals is the cultural traits of the country in which they live in [21]. As culture is effective in acquiring and developing personality traits [22], and it brings the individual a unique identity within the general rules.…”
Section: Introductionmentioning
confidence: 99%
“…Past literature posits that a user's level of online engagement is underpinned by the interplay of their personal characteristics, their surroundings, and features of the medium itself such as online flow [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Online flow has been defined as an individual's engagement/absorption in their online activity based on the progressive response to online demands, in a way that matches the rate of increase of an individual's performance to prevent boredom and maintain their consistent engagement [13][14].…”
mentioning
confidence: 99%
“…Online flow has been defined as an individual's engagement/absorption in their online activity based on the progressive response to online demands, in a way that matches the rate of increase of an individual's performance to prevent boredom and maintain their consistent engagement [13][14]. Moreover, the escalation of an individual's online flow experience has been related to problematic behaviours such as Internet Gaming Disorder [8][9][10][11][12]15,22]. This has triggered the development of various instruments to assess the construct [13,[18][19], including the five-item Online Flow Questionnaire (OFQ) [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation